Fungal pellets immobilized bacterial bioreactor for efficient nitrate removal at low C/N wastewater. (July 2021) - Zheng, Zhijie; Ali, Amjad; Su, Junfeng; Huang, Tinglin; Wang, Yue; Zhang, Shuai
Graphical abstract: Highlights: Fungal pellet, as natural biological carrier, can immobilize denitrifying bacteria. Fungal pellets immobilized bacterial bioreactor removed nitrate at low C/N ratio. The bioreactor was efficient for synthetic and real nitrate wastewater. High-throughput showed that GF3 was the dominant strain in bioreactor. Abstract: In this study, fungal pellets immobilized denitrifying Pseudomonas stutzeri sp. GF3 was cultivated to establish a bioreactor. The denitrification effect of fixed bacteria with fungal pellets was tested by response surface methodology (RSM). Analysis of the bioreactor showed that the denitrification efficiency reached 100% under the optimal conditions and the denitrification efficiency of the actual wastewater treatment in the stable phase reached 95.91%. Moreover, the organic matter and functional groups in the bioreactor under different C/N conditions were analyzed by fluorescence excitation-emission matrix (EEM) spectra and Fourier transform infrared spectroscopy (FTIR), which revealed that metabolic activities of denitrifying bacteria were enhanced with the increase of C/N. The morphology and structure of bacteria immobilized by fungal pellets explored by scanning electron microscope (SEM) showed the filamentous porous fungal pellets loaded with bacteria. Community structure analysis by high-throughput sequencing demonstrated that strain GF3 might was the dominant strain in bioreactor.